ASIMETRI INFORMASI DAN MANDATORY DISCLOSURE KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDARD: EFEK TERHAADAP RELEVANSI NILAI INFORMASI LABA DAN NILAI BUKU - Dhea Ayu Rosita Putri; Evi Rahmawati; Hafiez Sofyani (Media Riset Akuntansi, Auditing & Informasi, 2018)
This reasearch aimed to recognize the impact of information asimmetry and mandatory disclosure IFRS convergence toward value relevance of earnings and book value. The population in this study are manufakture companies listed on the  Indonesia Stock Exchange (IDX) year 2016. Sampling method that use is purposive sampling. The number of samples in this study are 68 samples. Types of data us is secondary data obtained from www.idx.co.id. Analysis technique used were Moderated Regression Analysis by SPSS 15.0. The results showed that the mandatory disclosure level of IFRS convergence increases the relevance of information on the value of earnings, the mandatory disclosure level of IFRS convergence does not increase the relevance of book information value, information asymmetry does not decrease the value relevance of earnings information, and information asymmetry decreases the relevance of book information value.